CONTRIBUTION TO THE HERPETOFAUNA OF SERBIA - DISTRIBUTION OF REPTILES IN KOSOVO AND METOHIJA PROVINCE - Tomović, Ljiljana; Timotijević, Magdalena; Ajtić, Rastko; Krizmanić, Imre; Labus, Nenad (Bulletin of Natural Sciences Research, 2018)
Kosovo and Metohija have already been recognized as regions with the highest diversity of reptiles in Serbia, where 92% (22 of 24) of existing reptile species can be found (Tomović et al., 2015a). First comprehensive contribution to herpetofauna of Kosovo and Metohija was provided by late Professor Gojko Pasuljević. In this study we present a complete dataset of distribution records for 13 most common reptile species in Kosovo and Metohija, including published and new distribution data compiled, and provide standardized 10 x 10 km UTM maps for these data. Results of this study include 1013 distribution records (278 new and 735 published data) for the following reptiles: Testudo hermanni, Ablepharus kitaibelii, Anguis fragilis, Lacerta agilis, Lacerta viridis, Podarcis muralis, Podarcis tauricus, Coronella austriaca, Dolichophis caspius, Natrix natrix, Natrix tessellata, Zamenis longissimus and Vipera ammodytes. The most widely distributed species, which occupy more than 50 UTM 10 x 10 km squares are: Podarcis muralis and Vipera ammodytes. Species with limited distribution which occupy less than 20 UTM 10 x 10 km are: Dolichophis caspius and Lacerta agilis. The largest numbers of new or confirmed literature data are recorded for: Anguis fragilis, Testudo hermanni and Vipera ammodytes. Having in mind that after 50 years, this is the first comprehensive study of the distribution of reptiles in Kosovo and Metohija exclusively, the presented faunistic data are far from being complete. Further systematic studies should provide a more complete insight into the distribution of herpetofauna of this province of Serbia.
Keywords: Herpetofauna; Faunistics; Serbia; Kosovo and Metohija